The Effect of Education Expenditure, Health Expenditure, and Infrastructure Expenditure on Education Levels, Health Quality and Sanitation in Regencies/Cities in Indonesia - Arituan, Bismart; Imansyah, Muhammad Handry; Sopiana, Yunita (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the effect of government expenditure on the number of people who graduate from elementary school, graduate from junior high school, literacy rate 15-24 years, literacy rate 15-55 years, school participation rate 7-12 years, school participation rate 13-15 years, family planning users, immunization, users of water and sanitation in districts/cities in Indonesia. The instrument of this study used panel data regression, which uses panel data of 2016-2019 in districts/cities in Indonesia. The panel data estimation technique used is the standard effect, fixed-effect, and random effect models. Government expenditure is measured using expenditure on education, expenditure on health, and expenditure on infrastructure. The results obtained are that government expenditure on education has a significant effect with 5% on the number of people who graduate from elementary school, the literacy rate of 15-55 years, and the school participation rate of 13-15 years in districts/cities in Indonesia. In the health sector, government expenditure significantly affects family planning users in regencies/cities in Indonesia. In contrast, government expenditure in infrastructure significantly affects users of safe water and the availability of sanitation in regencies/cities in Indonesia.